Linear dynamic analysis and active control of space prestressed taut cable net structures using wave scattering method. Issue 4 (22nd October 2015) - Wang, Zuowei; Li, Tuanjie
Summary: In this paper, the linear dynamic analysis and active control of prestressed taut cable net structures are investigated by the wave scattering method. Wave motion equations of cables are firstly derived to obtain the wave dispersion characteristics, which are the combinations of the longitudinal tensile wave equations of bars and transverse wave equations of taut strings. The waveguide and scattering matrices of cables are then formed by the force balance and displacement boundary conditions. The derivation of the traveling wave model of cable net structures is accomplished by combining systematic scattering matrix with transmission matrix. Finally, the wave active control method is proposed based on the established traveling wave model. The comparison of results obtained by the wave scattering method with the finite element method shows an excellent agreement. But more importantly, it demonstrates that the computational efficiency of the wave scattering method is higher for dynamic analysis of large‐scale cable net structures. The effectiveness of the proposed wave active control method is verified by a planar cable net structure. Copyright © 2015 John Wiley & Sons, Ltd.